Prevalence and Management of Pain by Different Age Groups of Korean Cancer Patients. (June 2013) - Kim, Jin Y.; Jang, Won Y.; Hur, Mi H.; Lee, Kang K.; Do, Young R.; Park, Keon U.; Hong, Young S.; Song, Hong Suk
The aims of this study were to evaluate the differences in cancer prevalence and pain management between young and elderly patients. The patients were grouped into 3 groups. The prevalence of cancer pain was 50.0% in those younger than 65 years, 55.9% in those aged between 65 and 75, and 58.3% in those older than 75 years. The prevalence of cancer pain was higher for patients in advanced stages and with poor performance status. Using logistic regression analysis, we found that performance status has a significant correlation with cancer pain. Severe cancer pain occurred in 8.0% of the patient and was most prevalent in the advanced stage. Side effects of analgesics were observed in 24.5%. Cancer pain correlates with performance status and cancer stage but not significantly with age.